Tantangan dan Strategi Guru Bahasa Arab dalam Menghadapi Plagiarisme Siswa di Era Large Language Models (LLM) Dalam Perspektif Teori Kontruktivisme: (Tahaddiyat wa Istiraatijiyyat mu’allim Al-lughah Al-‘arabiyah fii Muwajihati Intihali A’mali athu-Thullab fi ‘Ashri Namudzaj Al-lughah Al-Kabirah (LLMs) min Nadzhriyati Al-Binaiyah) - adilah, halfa; Muhammad Ibnu Supriyadi; Atika Mahda Salsabila; Akhmad Aufa Syukron (Program Studi Pendidikan bahasa Arab IAIN Langsa, 2025)
This study explores the challenges and strategies of Arabic language teachers in addressing student plagiarism in the era of Large Language Models (LLMs) from a constructivist learning perspective. The research is motivated by the increasing use of artificial intelligence tools that provide instant answers, which potentially reduce students’ critical thinking and original learning processes. The objective of this study is to describe forms of student plagiarism, patterns of LLM utilization in Arabic learning, and effective teacher strategies to maintain academic integrity. The research subjects were documents and scientific articles related to AI use in education, selected through purposive sampling. This study employed a qualitative descriptive approach using a library research method. The research instruments consisted of document analysis sheets. Data were collected through literature review and documentation, and analyzed using content analysis techniques involving coding, categorization, and thematic interpretation. The findings indicate that while LLMs contribute positively to vocabulary enrichment, translation practice, and adaptive learning, they also increase the risk of plagiarism due to students’ dependency on instant outputs. Teachers face challenges in students’ digital literacy and ethical awareness. Effective strategies include process-based assessment, reflective tasks, portfolio-based evaluation, and strengthening AI literacy. In conclusion, LLM integration in Arabic learning requires pedagogical adaptation and clear ethical guidelines so that technology functions as a learning aid rather than a substitute for students’ intellectual work.